Brief Report: Child Sexual Abuse Inquiries in Hong Kong, 2000–2017. Issue 1 (2nd January 2019) - Cheung, Monit; Leung, Carol A.; Chen, Xin; Leung, Patrick; Liu, Elaine Suk-Ching
Abstract: Community advocates in Hong Kong found no formal curriculum on child sexual abuse (CSA) prevention and started a newspaper column in 1999 to disseminate public education. This study analyzed the inquiries sent to this prevention column from 2000 to 2017. Content analysis found that, in 515 inquiries, 170 (33%) reported CSA incidents. Based on age information in 147 incidents, female abusers ( n  = 28) targeted victims averaging 6.48 years of age, which is 3.08 years significantly younger than those abused by male abusers ( n  = 119). In 82 inquiries with abusers' age information, 42 minor "abusers" were reported. Early sex education is highly recommended.